An Analytic Adjustment of a Sounding Line - Campbell, Andrew C.; Osborn, Roger T. (The International Hydrographic Review, 2015)
Horizontal data consisting of positional fixes, ship’s heading, and an average constant speed of advance, may be utilized in the adjustment of a sounding line. The adjustment technique of variation of coordinates resolves the horizontal data into the most probable line determination. Proof for the quality of the adjustment is established by the comparison o f depth differences (residuals) at line crossings. The quality of each line is indicated by a standard error which reflects the consistency of the horizontal data comprising each line. The residuals at the line crossings indicate the quality of the entire chart. Translation of the depth residuals into horizontal shifts, with a subsequent determination o f a standard error of these shifts, reflects the consistency of both the horizontal and vertical data comprising a chart. A comparison of the standard graphic method of adjustment is made with this new adjustment method.